The Influence of Using the Vn Application on the Poetry Learning Motivation of Class X Students of SMA Negeri 7 North Luwu - Cici Nurul Aulia; Andi Adam; Nur Khadijah Razak (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research is to determine the effect of using the VN application on the motivation to learn poetry in class X students at SMA Negeri 7 North Luwu. This type of research is Pre-Experimental Design (non design). The population in this study were students of SMA Negeri 7 North Luwu with selected samples from class X.1 of SMA Negeri 7 North Luwu. The assessment instruments used in this research are observation, documentation, and observation results test sheets. The data collection technique is by using documentation and tests. The analysis used in this research is descriptive analysis and inferential analysis. The results of this research show that the use of the VN application can be used as a medium in learning Indonesian, especially reading and musicalizing poetry because it can provide efficiency in learning and effectiveness for students in demonstrating reading and musicalizing poetry, thereby increasing student learning motivation. This was obtained from processing the hypothesis. 2.378 is greater than the critical value of t (2.032), meaning that H0 is rejected and H1 is accepted. Thus, the results of the hypothesis test show that using the VN application in editing videos of reading and musicalizing poetry significantly increases students' learning motivation compared to using the default smartphone editing application at SMA Negeri 7 North Luwu. Keywords : VN Application, Learning Motivation, Poetry